Mean Change in Refractive Status After Levator Muscle Resection in Patients of Simple Congenital Ptosis - Mohsin Javaid, Rana Muhammad; Chaudhary, Nasir; Habib, Rehab; Khan, Asad Aslam; Siddique, Kashif (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the mean change in refractive status after Levator muscle resection in patients of simple congenital ptosis. Study Design: Quasi Experimental study. Place and Duration of Study: This study was carried out at Institute of Ophthalmology, King Edward Medical University, Mayo Hospital Lahore, from 2014 to 2015. Material & Methods: Fifty patients were selected under the age of 12 years with no sex predilection presenting with simple congenital ptosis of pupil sparing type. Patients with neurogenic, aponeurotic ptosis, mechanical ptosis, Blepharophimosis syndrome, patients with previous failed ptosis surgery and patients with corneal anomalies were excluded. After history and examination, Cycloplegic retinoscopy was done, which was repeated after surgical intervention. All interventions were done by a single ophthalmic surgeon. The patients were examined and discharged on the second post operative day. All data including preoperative and postoperative recordings of spherical and cylindrical values were collected on a self-designed proforma. Follow up period was extended to 3 months. At 3rd month cycloplegic retinoscopy was done and change in character of refractive status was analyzed. Mean change in refractive status was calculated by difference of preoperative and postoperative sphere and cylinder values. Results: Mean age of patients was 4.26 ± 3.78 years. Mean change in spherical value after treatment was 0.447 ± 0.339. This difference was statistically significant with p-value = 0.000. While mean change in cylindrical value after treatment was 0.640 ± 0.580. This difference in cylinder value after treatment was also statistically significant with p-value = 0.000. Conclusion: Levator muscle resection has a significant effect on refractive status of the patients with congenital ptosis.